2021
DOI: 10.1038/s41388-021-01971-7
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback regulation of lncRNA PVT1 and HIF2α contributes to clear cell renal cell carcinoma tumorigenesis and metastasis

Abstract: Long noncoding RNAs (lncRNAs) have been reported to exert important roles in tumors, including clear cell renal cell carcinoma (ccRCC). PVT1 is an important oncogenic lncRNA which has critical effects on onset and development of various cancers, however, the underlying mechanism of PVT1 functioning in ccRCC remains largely unknown. VHL deficiency-induced HIF2α accumulation is one of the major factors for ccRCC. Here, we identified the potential molecular mechanism of PVT1 in promoting ccRCC development by stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…NICI was highly expressed in ccRCC, and its expression could be regulated by VHL 34 . PVT1 interacted with HIF2α protein to enhance its stability by protecting it from ubiquitin-dependent degradation, thereby contributing to the development and metastasis of ccRCC 16 . During this study, our result determined that overexpression of VHL upregulated the expression of APCDDL-AS1 and knockdown of VHL inhibited APCDD1L-AS1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NICI was highly expressed in ccRCC, and its expression could be regulated by VHL 34 . PVT1 interacted with HIF2α protein to enhance its stability by protecting it from ubiquitin-dependent degradation, thereby contributing to the development and metastasis of ccRCC 16 . During this study, our result determined that overexpression of VHL upregulated the expression of APCDDL-AS1 and knockdown of VHL inhibited APCDD1L-AS1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lncRNAs also play important roles in the development of ccRCC. For example, ZNF582-AS1 restrained the growth and metastasis of ccRCC by regulating the N(6)-methyladenosine modification of MT-RNR1 15 , and PVT1 promoted the tumorigenesis and metastasis of ccRCC by stabilizing HIF2α 16 . APCDD1L-AS1 was a novel lncRNA and located at Chromosome 20: 58,515,379-58,619,888.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also verified lncRNA PVT1 to be an oncogenic lncRNA in ccRCC. It has been reported that ccRCC has the strongest upregulated expression of PVT1 among all cancer types and served as a prognostic factor of renal cancer [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al. [ 175 ] found that HIF-2α promotes PVT1 expression by binding to the PVT1 enhancer; similarly, PVT1 can protect HIF-2α from ubiquitin-dependent degradation. This PVT1/HIF-2α loop promotes tumorigenesis and metastasis in RCC (Fig.…”
Section: Role Of Pvt1 In Various Human Tumorsmentioning
confidence: 99%